Management Model for University Cooperation at the Universidad TÃ©cnica De ManabÃ, Ecuador - Briones, Vicente FÃƒÂ©lix VÃƒÂ©liz; Entenza, Norberto PelegrÃƒÂn; GÃƒÂ¡mez, MarÃƒÂa RodrÃƒÂguez; CedeÃƒÂ±o, Monserrate Ruiz (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
In researching a management model for university cooperation at the Universidad TÃ©cnica de ManabÃ, with its components, phases, stages, input, and output information as well as the premises of its practical application, thereby achieving qualitative and quantitative changes proposed in the conception of university cooperation for sustainable development. the model for the management of cooperation, the assumptions of the model and the components are exposed, and a map with universities that are currently on the network and the issues raised in the strategy, setting out the results at national and international levels.